KONSEP LIMINALITAS DALAM RITUAL ANDHERENAT - Hilmy, Ayu Nur Izzati; Kusdiwanggo, Susilo; Yusran, Yusfan Adeputera (Studi Budaya Nusantara, 2024)
Liminality is a concept referring to the transitional phase in which individuals or groups experience a suspension ofhierarchy and social structure, fostering a sense of togetherness, collective solidarity, and equality. The andherenat ritual on Gili Iyang Island, Sumenep Regency, is a tradition of the migrant Buton-Binongko community aimed at invoking rain and maintaining soil fertility. This study explores and analyzes liminality in the andherenat ritual and its sociocultural implications for the assimilative community. A qualitative method and case study strategy were used, focusing on the cultural activities of the andherenat ritual. The research findings reveal that the andherenat ritual involves three phases of liminality: separation, liminality, and incorporation. The separation phase is marked by theperformance of tawassul, yasin, tahlil, and praise, separating participants from everyday life. The liminality phase is a transitional period where participants undergo spiritual transformation through activities such as the topak loberprocession and circling the island. The incorporation phase reintegrates participants into society with renewed identities, highlighted by a communal feast.